TEKNIK EDITING FILM DOKUMENTER BELAJAR DARI TANAH ADAT BADUY DENGAN IMPLEMENTASI AUDIO SPATIALIZATION BERBASIS BANDLAB - Azzahra, Fatimah; Santoso, Hudi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Documentary film is an audiovisual medium that presents the reality of life in a factual and educational manner. This study aims to examine the mechanism of video editing techniques and the implementation of audio spatialization using BandLab in the documentary film “Belajar dari Tanah Adat Baduy” This study employs a qualitative descriptive approach with data collection techniques including observation, interviews, documentation, and literature study. The editing process was carried out through offline editing and online editing stages using the CapCut application, including footage screening, footage selection, video arrangement, video cutting, color grading, transition addition, text insertion, and backsound. The editing techniques applied consist of continuity editing, compilation editing, and a combination of both to maintain visual continuity and strengthen the documentary narrative. The implementation of audio spatialization was carried out through panning, volume adjustment, fade in, and fade out to create more realistic spatial and directional sound effects. The application of these techniques was able to produce a more immersive audiovisual experience, making the atmosphere of the Baduy community’s life feel more vivid for the audience